Design of an Automatic Relay-Based Switching System Using Battery and PV Voltage in Off-Grid Solar PV Lighting - Reza Satria Rinaldi; Afriyastuti Herawati; Ika Novia Anggraini; Mawardi (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2026)
The use of solar energy through off-grid photovoltaic (PV) systems to meet energy demands—particularly for DC lighting —still requires further development to address challenges such as weather variability and other limitations. Additionally, an effective control process for valve-regulated lead-acid (VRLA) batteries is crucial to prevent rapid degradation and shorten lifespan. This control ensures charging starts when the depth of discharge (DoD) limit is reached and prevents simultaneous charging and discharging. This study proposes an integrated off-grid PV lighting system with control features. The system uses a low-cost, relay-based automation approach, known as SOL-ARSAT (Solar PV Off-Grid Lighting System with Relay Switching Automation Technology). The system incorporates an AC power source as backup and applies three automatic switching controls based on battery and PV voltage. The results show that the system operates according to the designed control logic (logic 1 = active, 0 = inactive) and successfully manages power transfer between PV and AC sources. The control strategy prevents simultaneous charging and discharging, a prolonged low state of charge (SoC). As a result, the system improves lighting reliability and enhances battery protection, thereby extending the battery lifespan.